New opioid receptor modulators and agonists. Issue 2 (June 2018) - Kaye, Alan D.; Cornett, Elyse M.; Patil, Shilpa S.; Gennuso, Sonja A.; Colontonio, Matthew M.; Latimer, Dustin R.; Kaye, Aaron J.; Urman, Richard D.; Vadivelu, Nalini
Abstract : There has been significant research to develop an ideal synthetic opioid. Opioids with variable properties possessing efficacy and with reduced side effects have been synthesized when compared to previously used agents. An opioid modulator is a drug that can produce both agonistic and antagonistic effects by binding to different opioid receptors and therefore cannot be classified as one or the other alone. These compounds can differ in their structures while still possessing opioid-mediated actions. This review will discuss TRV130 receptor modulators and other novel opioid receptor modulators, including Mitragyna "Kratom, " Ignavine, Salvinorin-A, DPI-289, UFP-505, LP1, SKF-10, 047, Cebranopadol, Naltrexone-14-O-sulfate, and Naloxegol. In summary, the structural elucidation of opioid receptors, allosteric modulation of opioid receptors, new opioid modulators and agonists, the employment of optogenetics, optopharmacology, and next-generation sequencing of opioid receptor genes and related functionality should create exciting new avenues for research and therapeutic development to treat conditions including pain, opioid abuse, and addiction.